2013
DOI: 10.1021/jm4000984
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Design of Selective Inhibitors of Neuronal Nitric Oxide Synthase

Abstract: Nitric oxide synthases (NOSs) comprise three closely related isoforms that catalyze the oxidation of l-arginine to l-citrulline and the important second messenger nitric oxide (NO). Pharmacological selective inhibition of neuronal NOS (nNOS) has the potential to be therapeutically beneficial in various neurodegenerative diseases. Here we present a structure-guided, selective nNOS inhibitor design based on the crystal structure of lead compound 1 in nNOS. The best inhibitor, 7, exhibited low nanomolar inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The inhibitor K S values, determined from an imidazole displacement assay are reported in µM for each inhibitor of bsNOS. Isolation and characterization of NOS inhibitors marked by α were previously reported in (Delker et al, 2010), β in (Huang et al, 2013), γ in (Huang et al, 2014), δ in (Holden et al, 2013), ξ in (Jing et al, 2014), π in (Holden et al, 2013), σ in (Huang et al, 2012), φ in (Huang et al, 2014), ψ (Holden et al, 2014), ϑ in (Cinelli et al, 2014), ϕ in (Kang et al, 2015, unpublished data), and θ reported here.…”
Section: Figuresupporting
confidence: 58%
“…The inhibitor K S values, determined from an imidazole displacement assay are reported in µM for each inhibitor of bsNOS. Isolation and characterization of NOS inhibitors marked by α were previously reported in (Delker et al, 2010), β in (Huang et al, 2013), γ in (Huang et al, 2014), δ in (Holden et al, 2013), ξ in (Jing et al, 2014), π in (Holden et al, 2013), σ in (Huang et al, 2012), φ in (Huang et al, 2014), ψ (Holden et al, 2014), ϑ in (Cinelli et al, 2014), ϕ in (Kang et al, 2015, unpublished data), and θ reported here.…”
Section: Figuresupporting
confidence: 58%
“…Asn368 replaces Asp597 in eNOS (vide supra), and electrostatic or water-mediated contact with the latter residue has been previously implicated in high n/e selectivity. 26, 40 Disappointingly, this modification was ineffective: 13 and 14 are less potent than 6 . Loss of activity upon extensive homologation was seen previously for 2-aminoquinoline compounds, 18 hypothesized to result from sterically disfavored, suboptimal or partial interactions, or internal torsional strain.…”
Section: Resultsmentioning
confidence: 99%
“…The other aminopyridine ring of 3 was retained as an isostere of guanidine, and the middle aromatic linker and N 1 or N 2 -methyl substituted ethylenediamine tail were varied. Because substitution on the middle aromatic ring provided bioactivity during our previous exploration with symmetric molecules, 25 the middle aromatic linker was substituted with cyano, fluorine, trifluoromethyl, and substituted by pyridine. The molecules in Figure 3, having a truncated side chain and various substitutions of the middle aromatic ring, were synthesized and their inhibitory potencies were determined in vitro.…”
Section: Introductionmentioning
confidence: 99%